The digital butterfly effect: unleashing the Islamic Banking industry in a post-pandemic era. - Boulila, Hadjer; Metadjer , Widad; Elsayed, Ibrahim; Benbekhti, Seyf Eddine (European Journal of Islamic Finance, 2024)
This study draws on the parallelism between digitalization and the complexity of the Islamic banking industry (IBs) in a post-pandemic era. It examines the digital Butterfly Effect on the Islamic banking industry to promote tech-driven IBs through an empirical lens. The study constructs a Fintech adoption index (FADi). It uses a Bayesian vector Auto-Regressive model, causality tests and impulse response functions for yearly data from 2008 to 2022 to examine the possible magnified effect of adopting Fintech by the Islamic banking industry in Malaysia. Key findings suggest that embracing Fintech by the IBs enhances the profitability of the banks, which is measured by the return on asset and return on equity. In addition, the study reports a ripple effect of FADi on the broader spectrum of the Malaysian economy. This indicates that Fintech fosters economic growth, household consumption, financial and insurance services, and corporate taxes. On the other hand, Fintech adoption helps reduce the unemployment rate. The findings contribute to the literature by investigating the IB as a system within financial chaos theory and the possible Butterfly Effect triggered by Fintech adoption.